Youth and the Labor Market: Between Ambition and Social Reality: An Analytical Study (Comprehensive Journal of Science, 2026)
This study addresses the issue of youth and the labor market as one of the contemporary social issues of increasing importance, due to its direct implications for social stability and development pathways. The study aims to analyze the reality of youth in the labor market and to identify the most prominent challenges they face, with a focus on the gap between youth aspirations and the social reality of the labor market, from a social work perspective.The study adopts a descriptive-analytical approach through analyzing relevant theoretical literature and previous studies. Findings from several prior studies, including Al-Tarawneh (2014), which examined organizational behavior and its relationship to the work environment, and Abdul Latif (2011), which addressed the fields of social work, indicate that youth face a range of difficulties in integrating into the labor market. These challenges include limited employment opportunities, weak alignment between educational outputs and labor market needs, as well as shortcomings in social policies supporting the economic and social empowerment of youth. Such factors contribute to widening the gap between individual aspirations and the existing social reality.The study concludes that addressing the issue of youth and the labor market requires adopting integrated social and professional interventions, along with activating the role of social work in preparing youth for the labor market, developing their skills, and enhancing their ability to adapt to social and economic transformations, thereby contributing to social integration and sustainable development.
Keywords: Youth, Labor Market, Unemployment, Aspirations, Social Reality